2016
DOI: 10.1016/j.ahj.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient factors associated with quality of life in atrial fibrillation

Abstract: Background As treatment options for atrial fibrillation (AF) increase, more attention is focused on patients’ experiences and quality of life (QoL). However, little is known about the factors associated with these outcomes. Methods The Atrial Fibrillation Effect on QualiTy-of-life (AFEQT) is a disease-specific QoL tool for AF, with domain and summary scores ranging from 0 (the worst QoL) to 100. Using multivariable linear regression, we evaluated factors associated with baseline AFEQT Summary and Subscale Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
3
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 38 publications
4
42
3
3
Order By: Relevance
“…Women were more likely to report AF symptoms and poor AF-related quality of life than men. While previous studies have substantiated this association between sex and AF symptoms and quality of life [28, 53], cohort studies have found that women are less likely to receive rhythm control treatments that reduce symptom severity [5456]. Symptoms of anxiety and depression were significantly more prevalent in women.…”
Section: Discussionmentioning
confidence: 98%
“…Women were more likely to report AF symptoms and poor AF-related quality of life than men. While previous studies have substantiated this association between sex and AF symptoms and quality of life [28, 53], cohort studies have found that women are less likely to receive rhythm control treatments that reduce symptom severity [5456]. Symptoms of anxiety and depression were significantly more prevalent in women.…”
Section: Discussionmentioning
confidence: 98%
“…For our sample size calculation, we assumed an SD in the AFEQT score ranging from 16 to 24 units, consistent with prior literature and a smaller-sized, single-arm demonstration of our intervention [ 4 , 18 , 19 ]. With an estimated population mean difference of 12 points between the intervention and control arms and an SD of 22 points, a total sample size of 120 participants would have 85% power to show a difference between the intervention and control groups.…”
Section: Methodsmentioning
confidence: 99%
“…The main AF symptoms are fatigue, decreased exercise tolerance, dyspnea and palpitations, which lead to decreased QoL in 58% of cases (Randolph et al, 2016 ). Exercise capacity and cardiopulmonary fitness will also be reduced to varying degrees (Ariansen et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%